2017
DOI: 10.1136/bmjopen-2017-017214
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic stress disorder in adult victims of cluster munitions in Lebanon: a 10-year longitudinal study

Abstract: ObjectiveThis study aims to explore the short-term and long-term prevalence and effects of post-traumatic stress disorder (PTSD) among victims of cluster munitions.Design and settingA prospective 10-year longitudinal study that took place in Lebanon.ParticipantsTwo-hundred-and-forty-four Lebanese civilian victims of submunition blasts, who were injured in 2006 and were over 18 years old, were interviewed. Included were participants who had been diagnosed with PTSD according to the Diagnostic and Statistical Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 52 publications
3
23
1
Order By: Relevance
“…Our study showed that the mean age in PTSD diagnosed patients was 32.84, and has semblance to other studies reported in the literature. It has been reported that psychological turbulence secondary to a traumatic incident can be overcome by good family support to the patient . Our study shows that patients with less family support exhibited a higher incidence of PTSD, and this was found to be statistically significant.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Our study showed that the mean age in PTSD diagnosed patients was 32.84, and has semblance to other studies reported in the literature. It has been reported that psychological turbulence secondary to a traumatic incident can be overcome by good family support to the patient . Our study shows that patients with less family support exhibited a higher incidence of PTSD, and this was found to be statistically significant.…”
Section: Discussionsupporting
confidence: 60%
“…It has been reported that psychological turbulence secondary to a traumatic incident can be overcome by good family support to the patient. 26 Our study shows that patients with less family support exhibited a higher incidence of PTSD, and this was found to be statistically significant.…”
Section: Discussionmentioning
confidence: 47%
“…Studies using the term “organised religiosity” were also included here. Religiosity as a predictor of lower severity of PTSD symptoms was demonstrated in Currier, Drescher, and Harris (), Currier, Holland, and Drescher (), Ali, Farooq, Bhatti, and Kuroiwa (), Fares et al (), Israel‐Cohen, Kaplan, Noy, and Kashy‐Rosenbaum (), and Sharma et al (); it predicted lower levels of other types of symptoms in Currier, Mallot, Martinez, Sandy, and Neimeyer (), Finklestein, Laufer, and Solomon (), and Kopacz, Currier, and Pigeon (). Wang, Wang, and Han () showed nonsignificant or negligible associations.…”
Section: Resultsmentioning
confidence: 95%
“…For socioeconomic status, there are more general reasons to expect interactions since it has been suggested in the life course literature that high parental resources provide a buffer against the adverse effects of all sorts of negative life events (Mandemakers, 2011). Finally, it has been argued that religiosity provides a coping style for dealing with negative war experiences (Bryant-Davis & Wong, 2013;Fares et al, 2017) and it is possible that this also will benefit the children who were not themselves exposed to war.…”
Section: Parents?mentioning
confidence: 99%